Pengaruh Pembelajaran Inkuiri Terbimbing Berbantuan Worksheet terhadap Kemampuan Berpikir Kritis Siswa pada Materi Bioteknologi - Koriatul Jannah Siregar; Wina Dyah Puspita Sari (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
Critical thinking skills are among the essential competencies required for students to meet the challenges of the 21st century. However, students' critical thinking skills in biotechnology remain relatively low and need to be enhanced through the implementation of learning models that promote active participation in the learning process. This study aims to determine the effect of the Guided Inquiry learning model assisted by Student Worksheets on students' critical thinking skills in Biotechnology material at UPT SMP Negeri 35 Medan. This study used a quasi-experimental method with a non-equivalent control group design. The population consisted of all grade IX students of UPT SMP Negeri 35 Medan. The sample was selected using purposive sampling, with class IX-1 as the experimental class and class IX-3 as the control class. The research instrument was a validated two-tier multiple-choice test designed to measure students' critical thinking skills. Data analysis using the Independent Samples T-test showed a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant effect of the Guided Inquiry model assisted by worksheets on students' critical thinking skills. The experimental class showed a higher average improvement (55.38%) than the control class (44.51%). All indicators of critical thinking clarification, assessment, inference, and strategy improved significantly in the experimental class. Therefore, the Guided Inquiry learning model assisted by worksheet is effective in improving students' critical thinking skills in Biotechnology material.